Synapsin peptide fused to E. coli heat-labile toxin B subunit induces regulatory T cells and modulates cytokine balance in experimental autoimmune encephalomyelitis - Scerbo Jaureguiberry, Maria Julia (2012)
We previously found that the preventive oral administration of a hybrid consisting of the C domain of synapsin and the B subunit of E. coli heat-labile enterotoxin (LTBSC) efficiently suppresses experimental autoimmune encephalomyelitis (EAE) development in rats. We investigated the effect of LTBSC on cytokine expression and on regulatory T (Treg) cells in rats with myelin induced EAE. LTBSC treatment increased the frequency of CD4 +FoxP3 + Treg cells in lymph nodes prior to challenge and in the EAE acute stage. LTBSC also up-regulated the expression of anti-inflammatory Th2/Th3 cytokines and diminished myelin basic protein-specific Th1 and Th17 cell responses in lymph nodes. CD4 +CD25 + Treg cells from LTBSC treated rats showed stronger suppressive properties than Treg cells from controls in vitro. Our observations indicate that LTBSC is a useful agent for modulating the autoimmune responses in EAE. © 2011 Elsevier B.V.